On the diversity of F420-dependent oxidoreductases: A sequence- and structure-based classification - Mascotti, María Laura (2021)
The F420 deazaflavin cofactor is an intriguing molecule as it structurally resembles the canonical flavin cofactor, although behaves as a nicotinamide cofactor due to its obligate hydride-transfer reactivity and similar low redox potential. Since its discovery, numerous enzymes relying on it have been described. The known deazaflavoproteins are taxonomically restricted to Archaea and Bacteria. The biochemistry of the deazaflavoenzymes is diverse and they exhibit great structural variability. In this study a thorough sequence and structural homology evolutionary analysis was performed in order to generate an overarching classification of the F420-dependent oxidoreductases. Five different deazaflavoenzyme Classes (I–V) are described according to their structural folds as follows: Class I encompassing the TIM-barrel F420-dependent enzymes; Class II including the Rossmann fold F420-dependent enzymes; Class III comprising the β-roll F420-dependent enzymes; Class IV which exclusively gathers the SH3 barrel F420-dependent enzymes and Class V including the three layer ββα sandwich F420-dependent enzymes. This classification provides a framework for the identification and biochemical characterization of novel deazaflavoenzymes.